2011
DOI: 10.1016/j.thromres.2011.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Engineered virus-like nanoparticles reverse heparin anticoagulation more consistently than protamine in plasma from heparin-treated patients

Abstract: Heparin is widely used for anticoagulation, often requiring the subsequent administration of a reversal agent. The only approved reversal agent for heparin is protamine sulfate, which induces well described adverse reactions in patients. Previously we reported a novel class of heparin antagonists based on the bacteriophage Qβ platform, displaying polyvalent cationic motifs which bind with high affinity to heparin. Here we report heparin reversal by the most effective of these virus-like particles (VLP) in samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…134 In patient samples, the modied Qb capsids also showed heparin reversal, even if high doses of heparin were administered to the patients. 135 In comparison to protamine, more consistent results were obtained for the VLPs.…”
Section: Virus-like Particlesmentioning
confidence: 67%
“…134 In patient samples, the modied Qb capsids also showed heparin reversal, even if high doses of heparin were administered to the patients. 135 In comparison to protamine, more consistent results were obtained for the VLPs.…”
Section: Virus-like Particlesmentioning
confidence: 67%
“…In clinical trials patients' safety is paramount, therefore potential toxicity of new candidates for drugs is the most important issue. A number of compounds that have been primarily introduced as very effective antidotes of heparins such as delparantag (PMX-60056) (Mahan, 2014 ), REG1 Anticoagulation System (Burke, 2015 ), PM102 (Cushing et al, 2010 ), virus-like nanoparticles (VLP) (Gale et al, 2011 ) or HepArrestTM (Shenoy et al, 1999 ), later in the preclinical and even in the clinical trials revealed unacceptable side effects and failed.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly promising VLP for biomedical applications is bacteriophage Qβ, an icosahedral nanoparticle 28 nm in diameter that is composed of 180 copies of a 132 amino acid, 14.1 kDa coat protein. , The capsid has good stability toward extremes in pH and temperature, can tolerate a range of modifications made to its surface either through mutation or chemically post-assembly, and can be expressed in E. coli in a high yield. Our group has examined various applications of Qβ; current investigations delve into exploring the ability of Qβ variants to antagonize the anticoagulant activity of heparin. Heparin is a naturally occurring glycosaminoglycan derived primarily from porcine tissue as a heterogeneous mixture of polysaccharides with variable molecular weight (5–30 kDa) and degree of sulfation. , Its anticoagulant activity is due largely to the activation of antithrombin, which inactivates the coagulation serine proteases thrombin and factor Xa. , First put into use clinically in the 1940s, heparin remains the primary anticoagulant used today.…”
Section: Introductionmentioning
confidence: 99%